University Student Satisfaction and Skill Acquisition: Evidence from the Undergraduate Dissertation - Fidel Martínez-Roget; Pilar Freire Esparís; Emilia Vázquez-Rozas (MDPI AG, 2020)
One of the main objectives of the Undergraduate Dissertation is to evaluate the skills associated with a degree. Student satisfaction with the training and skills acquired can be an indicator of the quality of higher education. This paper aims to analyse student satisfaction with Undergraduate Dissertation at the Faculty of Economics of the University of Santiago de Compostela (Spain). Based on a survey conducted among 130 students (75.7% of a total of 172 students who presented their UD during the academic year 2013−2014), structural equation modelling was applied to analyse the influence on satisfaction of aspects related to intellectual curiosity and the perception of acquired skills. The results show that the perception of the skills acquired play a crucial role in students’ satisfaction with Undergraduate Satisfaction, conditioned by their perceived future usefulness and backed by personality and motivation elements that encourage their acquisition. The results confirm the significant role played by the tutor, who emerges as an element that boosts the central relations of the model.